Comprehensive Insights into De Quervain’s Tenosynovitis: From Etiology to Rehabilitation - Charzewski, Piotr; Starzyk, Agnieszka (Quality in Sport, 2025)
De Quervain's tenosynovitis, a common condition affecting the first dorsal compartment of the wrist, is characterized by pain, swelling, and restricted tendon mobility, often resulting from repetitive manual tasks or biomechanical strain. This review integrates insights from three recent studies, emphasizing the multifactorial etiology, advanced diagnostic techniques, and evolving treatment modalities. Etiological factors include mechanical strain, anatomical variations, and degenerative changes, with ultrasonography emerging as a critical tool for enhancing diagnostic accuracy and guiding therapeutic strategies. Conservative treatments such as splinting, corticosteroid injections, and occupational therapy remain the cornerstone of management, while surgical decompression offers definitive relief for refractory cases. Emerging rehabilitative approaches, including graded tendon-loading protocols, and innovations in imaging and therapy, highlight a shift toward more precise and patient-centered care. Despite advancements, challenges persist in optimizing treatment protocols and addressing long-term functional recovery. Further research is essential to refine diagnostic and therapeutic strategies, reduce recurrence rates, and improve patient outcomes.